Uses of regulators and non-specific compounds on the germination of licuri seeds (Syagrus coronata (Mart.) Becc) - Carvalho, Noeli O. S.; Pelacani, Claudinéia R.; Rodrigues, Manuela O. de S.; Crepaldi, Iara C. (SITIENTIBUS série Ciências Biológicas, 2005)
The slow and irregular germination pattern of palm tree seeds justifies the use of mechanisms to speed up the germination process. This article looks at the germination effects of licuri seeds (Syagrus coronata (Mart.) Becc) when they were imbibed in water, as well as in a solution containing gibberellic acid, and another containing thiourea. The water imbibition had a great effect on the germination and germination speed of endocarp seeds. For seeds without endocarp, however, treatment caused tissue deterioration, reducing germination rate. High levels of gibberellic acid solutions increased germination rate of seeds submitted to 12-48 hours of imbibition, resulting in 65% and 52% respectively. Thiourea promoted the highest germination and germination speed during the 12 hour treatment period. Data suggest that the presence of endocarp on licuri seeds influences the germinative process. The exposure of seeds to water and thiourea solutions for 12 hours was the most recommended treatment to promote the germination of seeds.